2014
DOI: 10.1007/s00330-014-3430-4
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of noncalculous periampullary obstruction: comparison of CT with negative-contrast CT cholangiopancreatography versus MRI with MR cholangiopancreatography

Abstract: • nCTCP with subvolume MinIP is a practical tool in evaluating biliary obstruction • Two image sets have a comparable performance in differentiating noncalculous periampullary obstruction • MDCT could serve as an alternative in patients not eligible for MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Previous studies have provided the observation that overall survival was highest for patients with ampullary and duodenal cancers, intermediate for patients with bile duct cancers, and lowest for those with pancreatic cancers . Therefore, many investigators tried to differentiate the four types of tumor using different imaging techniques in order to predict patients' prognosis . However, due to the anatomical complexity of the periampullary region, correct classification with respect to location remains challenging, particularly if the tumor is large and involves more than one potential site of origin .…”
mentioning
confidence: 99%
“…Previous studies have provided the observation that overall survival was highest for patients with ampullary and duodenal cancers, intermediate for patients with bile duct cancers, and lowest for those with pancreatic cancers . Therefore, many investigators tried to differentiate the four types of tumor using different imaging techniques in order to predict patients' prognosis . However, due to the anatomical complexity of the periampullary region, correct classification with respect to location remains challenging, particularly if the tumor is large and involves more than one potential site of origin .…”
mentioning
confidence: 99%
“…The imaging principle is based on the dilated bile ducts as a negative contrast agent for differentiation from the surrounding enhanced hepatic and pancreatic parenchyma without additional biliary contrast agent [12] . This technique was useful for identifying obstructive level, depicting complex biliary tree anatomy, and providing entire pancreatobiliary system in one image similar to of 3D MR cholangiopancreatography [13] ( Fig. 1 , Fig.…”
Section: Image Postprocessingmentioning
confidence: 99%
“…But its value is still unsatisfying in the diagnosis in periampullary lesions. Previous studies have reported that the specificity was 75.68-100%, sensitivity was 60-100%, and accuracy was 91.17-92.92% in the diagnosis of periampullary space-occupying lesions [11][12][13][14]. Then, MRCP examination requires a magnetic field, which is contradicted for patients with metal implanted material, such as cardiac pacemaker, metal stent, etc.…”
Section: Introductionmentioning
confidence: 99%